Integrating Islamic Values and Scientific Knowledge Through Artificial Intelligence: Transforming Curriculum Design in the Society 5.0 Era - Fika Umul Muliyanti; Desti Fajriyanti (Journal of Innovation and Research in Primary Education, 2026)
Contemporary Islamic education faces persistent challenges in integrating religious values with scientific knowledge, resulting in fragmented student development. This study examines how artificial intelligence, specifically Gemini AI, facilitates systematic curriculum integration within Islamic educational institutions in the digital era. Employing qualitative descriptive-analytical design, this research was conducted at MI Ma'arif NU 1 Pageraji, Indonesia, involving six Islamic education teachers. Data collection utilized triangulation methods including participatory observation, in-depth semi-structured interviews, and comprehensive document analysis. Thematic analysis following Creswell's framework identified integration patterns and implementation challenges. Findings reveal that AI-mediated curriculum development reduces teacher planning time by approximately 40% while producing more comprehensive integration schemes. The system automatically generates integration points connecting Islamic values with secular content across subject areas. However, all participating teachers expressed concerns regarding theological accuracy of AI-generated Islamic content, necessitating collaborative verification mechanisms. Teachers adapted 78% of AI suggestions to align with developmental levels and cultural contexts, demonstrating pedagogical agency. The research introduces a "co-creative integration model" where AI provides structural scaffolding while teachers contribute contextual wisdom and theological verification. This asymmetric integration acknowledges differential requirements for validating secular versus religious knowledge. Findings contribute practical pathways for resource-constrained institutions to implement integrated curricula through strategic technology adoption coupled with robust verification mechanisms.